2017
DOI: 10.1155/2017/5762525
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cytomegalovirus Reactivation in Patient with Low-Grade Non-Hodgkin’s Lymphoma after Standard Chemotherapy

Abstract: Clinically significant cytomegalovirus (CMV) reactivation is not uncommon in patients with severe immunodeficiency secondary to underlying medical disorders or following aggressive immunosuppressive therapy. However, it is less frequently found in patients with low-grade haematological malignancies after nonintensive chemotherapy. We treated a patient at our centre for stage IVB follicular lymphoma with standard chemotherapy who successively developed CMV colitis associated with a CMV viral load of >3 million … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Clinical manifestations and severity of CMV reactivation vary among patients treated with bendamustine, from no symptoms to severe CMV disease and death [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], as also described in our cohort. In symptomatic patients, various antiviral agents are employed, such as ganciclovir and VGCV at 900 or 1,800 mg/daily [ 46 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Clinical manifestations and severity of CMV reactivation vary among patients treated with bendamustine, from no symptoms to severe CMV disease and death [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], as also described in our cohort. In symptomatic patients, various antiviral agents are employed, such as ganciclovir and VGCV at 900 or 1,800 mg/daily [ 46 ].…”
Section: Discussionsupporting
confidence: 66%
“…CMV reactivation develops early in bendamustine administration usually after the third cycle of therapy, as documented in several case reports [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]; however, no significant differences in long-term cumulative incidence of reactivation were registered in our cohort between patients who received less than three courses of bendamustine and subjects who had more than three cycles of therapy, while in multivariate analysis the number of cycles of bendamustine increased the risk of CMV reactivation in treatment-naïve patients who received bendamustine as first-line therapy. This augmented susceptibility to viral reactivation might be caused by an impairment in T cell immunity, such as decreased circulating levels of CMV-specific CD8 + cytotoxic lymphocytes and CD4 + T cells [ 19 , 28 , 31 , 34 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…To our knowledge, this is the first report of a disseminated CMV disease following treatment with bendamustine. While several case studies of localized CMV disease have been reported [12], no disseminated infection post-bendamustine has been described.…”
Section: Discussionmentioning
confidence: 99%